2008
DOI: 10.1063/1.2829598
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymer coating on the low-temperature photoluminescence properties of ZnO nanowires

Abstract: We report on low temperature photoluminescence studies of ZnO nanowires embedded in different polymers. Comparing the spectra of as-grown and embedded ZnO nanowires, we find a decrease of the deep-level emission and an increase of the near band-edge emission after the embedding process. The near band-edge emission of the embedded ZnO nanowires is dominated by a surface exciton band. The observed effects are independent of the selected polymer. The decrease of the deep-level emission scales with the balling abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 17 publications
4
83
1
1
Order By: Relevance
“…Studies have shown that annealing at 200 °C can largely reduce the defect concentration as evidenced by positron annihilation spectroscopy [349]. A polymer coating on the ZnO nanowires was also demonstrated to effectively depress the defect emission and enhance the near-band-edge emission [358]. A photoluminescence spectrum of ZnO nanowires at 4.2 K is shown in Fig.…”
Section: Photoluminescencementioning
confidence: 99%
“…Studies have shown that annealing at 200 °C can largely reduce the defect concentration as evidenced by positron annihilation spectroscopy [349]. A polymer coating on the ZnO nanowires was also demonstrated to effectively depress the defect emission and enhance the near-band-edge emission [358]. A photoluminescence spectrum of ZnO nanowires at 4.2 K is shown in Fig.…”
Section: Photoluminescencementioning
confidence: 99%
“…SX PL has been detected from nanostructures at low temperature [9][10][11], and from ZnO bulk single crystals or epitaxial layers [8,12]. Recently, we have observed a distinct SX PL band from a ZnO thin film covered with a molecular monolayer [12].…”
mentioning
confidence: 91%
“…Different types of excitons have been distinguished in the prototype wide gap semiconductor ZnO: free excitons (FX) with a binding energy of ~60 meV, excitons bound to different donor and acceptor atoms (DX), and surface excitons (SX) [5][6][7][8][9][10][11][12]. SX PL has been detected from nanostructures at low temperature [9][10][11], and from ZnO bulk single crystals or epitaxial layers [8,12].…”
mentioning
confidence: 99%
“…The biologically-inspired chemical sensor design utilizes available materials in a unique way to form a simple and elegant design. Considering manufacturability, the nanowires connected at both ends to a substrate (Figure 9a) could most likely utilize conventional microelectronic assembly and then be suspended into different polymer solutions [83] or use a polymer chemical vapor deposition technique [84] to coat the nanosprings. Further investigation is necessary to determine if the sensor elements suspended between two grids could be fabricated on the nano-scale.…”
Section: Final Conceptmentioning
confidence: 99%